Problematika Kinerja Penyuluh Keluarga Berencana Studi Kasus DP3AKB Kota Serang - Tarigan, Sri Ropika Dana; Stiawati, Titi (@-Publik: Jurnal Administrasi Publik, 2024)
Although family planning officers at the Women's Empowerment, Child Protection, and Family Planning Agency in the city of Serang demonstrate good performance, there is still room for improvement to achieve optimal levels. Therefore, the objective of this research is to conduct a thorough evaluation and analysis of the performance of family planning counselors. This study applies a qualitative descriptive method, involving interviews, document reviews, and observations as data collection methods. Various research instruments, such as interview guides, document reviews, and observations, are used to gather the necessary data. Data analysis is carried out carefully through the processes of data reduction, data presentation, drawing conclusions, and verification, with triangulation techniques used to ensure data accuracy. The research findings indicate that overall, the performance of family planning officers is considered satisfactory, although there are still some areas that need to be improved for the performance of Family Planning Counselors to be optimized.